Unilateral and Bilateral Hearing Aids for Age-Related Hearing Loss - Sherri L. Smith; Todd A. Ricketts; Kayla W. Kilpatrick; Rebecca North; Janet P. Bettger; Theresa Coles; Shari Eberts; Sarah B. Peskoe; Howard W. Francis; Heather Toth; William Dillon; Laura Thompson; et al. (JAMA Otolaryngology–Head & Neck Surgery, 2026)
Importance Age-related hearing loss (ARHL) is ubiquitous and is characterized as bilateral symmetrical sensorineural and mild to moderate in degree. When left untreated, significant impacts arise in domains including communication, psychosocial, cognitive and physical health. Data demonstrating the effectiveness of unilateral or bilateral hearing aids (HAs) as the standard treatment are lacking. Objective To determine whether bilateral HAs provide more benefit compared with a unilateral HA. Design, Setting, and Participants This single-blinded parallel-group randomized clinical trial was conducted at audiology clinics at Duke University Health System and Vanderbilt University from 2021 to 2024 with the primary outcome duration of 3 months. Participants were aged 50 years or older with ARHL with less than 3 months of prior HA use seeking HAs. Participants were randomly assigned to the bilateral or unilateral group. Analyses were based on intention to treat. Interventions Commercially available prescription receiver-in-the-canal HAs. Main Outcomes and Measures The hypothesis was that bilateral HAs would provide greater benefit than a unilateral HA. The primary outcome was HA benefit as measured using the Abbreviated Profile of Hearing Aid Benefit (APHAB) score. Benefit was defined as the difference in APHAB-global score at the 3-month primary end point (aided) from baseline (pretreatment/unaided) APHAB scores. The primary analysis was a linear regression of the APHAB benefit score at 3 months with clinical site and hearing aid assignment as covariates. Results A total of 275 participants were included (148 female [53.8%]; mean [SD] age, 70.9 [7.9] years). The mean (SD) APHAB benefit score was 14.41 (13.02) for the unilateral group (n = 136) and 19.74 (15.18) for the bilateral group (n = 139). These results indicate that both groups had benefit as demonstrated in APHAB benefit scores, with the bilateral group experiencing significantly higher benefit compared with the unilateral group with a mean difference in APHAB benefit score of −5.29% (95% CI, −8.79% to −1.80%) between the groups. Conclusions and Relevance The trial results indicate that bilateral HAs yield greater self-reported benefit than unilateral HAs; however, while statistically detectable, it is not clear whether this reaches the threshold for clinical meaningfulness. Both configurations produced individually meaningful improvements. These results inform, but do not yet establish, a standard-of-practice recommendation for bilateral fitting. Trial Registration ClinicalTrials.gov Identifier: NCT04739436